Evaluation of the use of piperacillin/tazobactam (Tazocin®) at Hamad General Hospital, Qatar: are there unjustified prescriptions? - Khan, Fahmi (Infection and drug resistance, 2012)
The aim of this study was to evaluate the appropriateness of piperacillin/tazobactam (Tazocin(®); Pfizer, New York, NY) usage in our hospital. This retrospective study was designed to involve all patients admitted to Hamad General Hospital and prescribed piperacillin/tazobactam as an empiric therapy from January 1 to March 31, 2008. The medical records of such patients were retrospectively reviewed and studied. During this period, 610 prescriptions were ordered for 596 patients. The main indication for initiation of Tazocin was sepsis (207/610; 34%). The overall rate of appropriateness of empirical therapy was 348/610 (57%). Most of the inappropriate prescriptions were in cases of aspiration pneumonia and abdominal infections, with inappropriate prescriptions found mostly in surgical wards (86%) and the surgical intensive care unit (66.7%). Septic work-up results showed positive cultures in 57% (345/610) of cases. There were 198/254 prescriptions (78%) where antibiotics were changed according to the sensitivity data to narrow-spectrum antimicrobials. In 56/254 (22%) cases, pathogens were susceptible to narrow-spectrum antibiotics even though piperacillin/tazobactam was continued. Our study showed that there was an injudicious use of piperacillin/tazobactam at our hospital, evidenced by the significant number of inappropriate empiric prescriptions and inappropriate drug modifications, based on the results of microbial cultures and antibiograms.